Croatian aquatic dance flies (Diptera: Empididae: Clinocerinae and Hemerodromiinae): species diversity, distribution and relationship to surrounding countries - Ivković, Marija; Gračan, Romana; Horvat, Bogdan (Zootaxa, 2013)
A checklist of aquatic Empididae (dance flies) from Croatia (36 species in subfamily Clinocerinae and 14 species in subfamily Hemerodromiinae) is presented, including information related to the Ecoregions in which species were found and specific species traits. Clinocerinae are represented by five genera, with Wiedemannia Zetterstedt being most species rich (20 species) and Clinocerella Engel least numerous with only one species. In Hemerodromiinae there are 8 species of Chelifera Macquart and 6 species and Hemerodromia Meigen. In addition, a discussion related to the species included and excluded from the list is provided. Most species are univoltine with adults emerging in Spring and Summer, although Kowarzia barbatula Mik and Wiedemannia (Eucelidia) zetterstedti (Fallén) are present throughout the year and Wiedemannia (Chamaedipsia) aequilobata Mandaron occurrs in Winter. The Croatian species assemblage is similar to the well-studied fauna of neighboring Slovenia (63 spp.). It is recommended that some rare species and the streams they inhabit should be considered for greater protection.